A igualdade sob a ótica filosófica política - Dourado, Jônatas Monteiro (2015)
As scientific scope, we will address a topic addressed by the doctrine and constantly debated by journalistic channels, a topic of great importance and social relevance. At all times of life, whether in the family bosom, in the workplace or even in public spaces, the proposed theme will always be there for both social relations as for actions, decisions and feelings, that is, at any time we face the equality. This work aims not only to demonstrate equality as a separate institute, but also as social and legal premise, it means, a need and social satisfaction that demonstrate real impact on society, being a subject covered directly by the Constitution. The great problematic is guided in the lack of appreciation of the fundamentals of equality, not enough to create methods to achieve it, as these can only be created when known indeed, the needs. These bases are available not only in the Federal Constitution, which guides the conduct and policies that should pursue these goals, but also in the facts of the world both in what happened as what happens today and what is to come, and thus we see that are not yet ready. We will mention some aspects related to equality, mainly dealing with inequality limits to allow the isonomic composition of a relationship, it means, what legal aspects and at what time we admit a difference to allow the equality. We can say on this complex point, that we are facing an egalitarian paradox and what we intend to address in this research is the paradoxical form of legal and social equality which becomes a fully strengthened institute under the Constitutional umbrella that makes up the social system that regulates autopoetically , covering with key players to resolve certain conflicts, maintain social equilibrium, safeguarding the democratic state into a federal republic that is Brazil, which is governed by a Constitution